Habitat and range extension of Cobaea lutea (Polemoniaceae) in western Mexico - Sahagún-Godínez, Eduardo; Lomelí-Sención, José Aquileo; Prather, L. Alan (Instituto de Ecología, A.C., 2001)
For the first time we present evidence of the presence of Cobaea lutea D. Don in tropical deciduous forest; we propose an hypothesis to explain this event and discuss the variety of habitats occupied by this and other members of the Polemoniaceae. We analyze the extension of the geographic limits of C. lutea ca. 350 km northwestwards from the “Sierra Madre del Sur” in Guerrero to the “Eje Neovolcánico” in Jalisco. We also document the presence of densely long-villous pedicels as a morphological variant of C. lutea, and present a description and an illustration.